Politics less danger than economy (economics)? The Relations between Media and Politics in the Opinion of German Journalists and Politicians - Szymańska, Agnieszka (Political Preferences, 2017)
The paper presents the results of the individual depth interviews (IDI) conducted with German press journalists (16) and politicians (21) from all levels of politics (local & regional, national and European) and the most important political parties in Germany (CDU/CSU, FDP, SPD, Die Linke, Die Grünen, Piraten Partei). The answers of the respondents relate to the role of the media in politics, the importance of informal relationship between journalists and politicians and the predictions of the media impact on politics in the future. Key words: the relation between politics and media, political communication, journalism research